Development of a multiplex real-time qRT-PCR for discriminating the predominant epidemic variant IBDV and very virulent IBDV - Wu, Ziwen; Yu, Hangbo; Wang, Guodong; Ling, Dan; Zhang, Yulong; Liu, Runhang; Ke, Erjing; Wang, Suyan; Zhang, Yanping; Liu, Yongzhen; Cui, Hongyu; Chen, Yuntong; et al. (Frontiers in Veterinary Science, 2026)
Infectious bursal disease (IBD) is an important immunosuppressive disease of chicken caused by infectious bursal disease virus (IBDV). At present, the newly emerging novel variant IBDV (varIBDV) and the persistently prevalent very virulent IBDV (vvIBDV) are two major threats, while the non-var/vvIBDV, such as classic IBDV (cIBDV) and attenuated IBDV (attIBDV), also increases the complexity of clinical detection. In this study, a multiplex real-time quantitative fluorescence RT-PCR (qRT-PCR) was developed. Based on sequence analysis of different pathogenic IBDV strains, three probes with different fluorescent signals (FAM, VIC, CY5) and two pairs of primers were designed. Specifically, varIBDV exhibits three fluorescent signals (FAM, VIC, CY5), vvIBDV shows two signals (FAM, VIC), and non-var/vvIBDV displays one signal (FAM). The method possesses excellent specificity: no cross-reactivity was observed between different pathogenic IBDV types, nor with other common avian pathogens. This method has good reproducibility and high sensitivity, with a minimum detection limit of about 10 copies. Furthermore, in the detection of laboratory or clinical samples, the consistency rate of this method with the conventional sequencing analysis method reached 100%. In conclusion, this study developed for the first time a multiplex qRT-PCR that can universally detect IBDV and simultaneously distinguish between vvIBDV and varIBDV, which is of great significance for high-throughput emergency detection and comprehensive prevention and control of new IBDV epidemics.